Perubahan Sifat Fisika Kimia Formulasi Pestisida Bentuk Emulsifiable Concentrate (EC) Dalam Penyimpanan - Nani Satiti (Jurnal Kimia dan Kemasan, 1987)
The formulation stability during storage is an important factor in emulsifiableconcentrate (EC) form of pesticide formulation. This stability including of emulsion stability and other chemical and physical characteristies of the formulation. So pesticide formulation chemical examination is necessary carried out for quality and safety guarantee during storage and transportation. The examination carried out on three sort of EC pesticide formulation samplethat is : x formulation with active ingredient Diazinon = 600 g/l.y formulation with active ingredient BPMC = 500 g/l. z formulation with active ingredient Diazinon .+ MIPC = 200 + 100 g/l.Those sample are store in time variation of 0,1,2, month in room temperature and followed by laboratory examination for emulsive stability, foam formulation,acidity, flash point and active ingredient.